Population genetics studies of Puccinia striiformis f. sp. tritici in Dagestan and Northwestern Russia - E. L. Shaydayuk; D. R. Yakovleva; K. M. Abdullaev; V. P. Pyukkenen; E. I. Gultyaeva (Труды по прикладной ботанике, генетике и селекции, 2021)
Background. Yellow rust (Puccinia striiformis West.) is a harmful disease of cereal crops. Significant yellow rust in cidence has systematically been registered on VIR’s experimental fields in Derbent (Dagestan) and Pushkin (North western Russia). Resistance assessment and subsequent selection of resistance sources for breeding require proper monitoring of the virulence in the pathogen’s local populations. The purpose of this work was to characterize the virulence of P. striiformis on VIR’s experimental fields in Derbent and Pushkin, and use molecular markers to find out whether the studied P. striiformis isolates belong to any of the most dangerous invasive groups PstS1 and PstS2.Materials and methods. In Derbent, leaves with uredinio pustules were collected from bread and durum wheat accessions; in Pushkin, from bread wheat and triticale plants. The pathogen’s virulence was analyzed in the laboratory using the world and European sets of differential cultivars, and isogenic Avocet Yr lines. In 2020, the resistance of differential sets was tested in the field in Derbent under a high natural infection pressure. SCAR markers were used to identify the invasive PstS1 and PstS2 isolates. Results and conclusion. A total of 18 phenotypes (races) of striiformis were identified (4 in Derbent, and 14 in Pushkin). The Yr5, Yr10, Yr15, Yr17, Yr24 and Yr26 genes manifested high effectiveness in both locations. In the field, immune responses were observed in the Avocet lines with the Yr5, Yr7, Yr8, Yr10, Yr15, Yr24 and YrAR genes, and in the differential cvs. ‘Vilmorin 23’, ‘Moro’, ‘Reichersberg 42’, ‘Heines Peko’, ‘Nord Desprez’, ‘Compare’, ‘Carstens V’, ‘Spaldings Prolific’ and ‘Heines VII’. Moderate resistance was recorded for the line Jupateco 73R (damage up to 5%), and cvs. ‘Heines Kolben’ and ‘Strubes Dickkopf’ (5–10%). Using molecular markers, 2 isolates from the invasive group PstS2 were identified in the Pushkin collection of P. striiformis.